PENGGUNAAN ANTIBIOTIK PADA TERAPI DIARE AKUT ANAK DI INSTALASI RAWAT JALAN PUSKESMAS BENDAN TAHUN 2012 - Isti Agitsah; Siska Rusmalina; Jamaludin Al J. Ef (LPPM Universitas Pekalongan, 2014)
Diarrhea disease cause death third of children in the world. The main causes diarrhea death is improper therapy management. To minimize the number of deaths due to diarrhea, especially in the town of Pekalongan, so necessary to do research to know percentage of antibiotic use and percentage types of antibiotics used in therapy of acute diarrhea children at installation of outpatient health centers bendan Pekalongan city in 2014. The method used in this study was descriptive with reference to secondary data retrieved from the medical records. Results of this study was the percentage of antibiotics used in the treatment of acute diarrhea in children outpatient health centers poly Bendan Pekalongan is 83.59%. consisting of 92.63% cotrimoxazole, chloramphenicol was 2.76%, 1.84% metronidazole is, tetracycline was 0.69%, 0.69% gentamicin is, 0.46% of amoxicillin, and 0.23% respectively for cefadroxil, neomycin, erythromycin also ketokonazole. Thus the treatment of acute diarrhea children in Outpatient Health Center Bendan Installation Pekalongan are appropriate and meet the requirements of Basic Medicine in health centers and BKPM (Public Lung Health Center). Keywords: Antibiotic, Acute Diarrhea, Children, health center